2002
DOI: 10.1128/aem.68.2.485-495.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Dehalococcoides 16S Ribosomal DNA from Chloroethene-Contaminated Sites throughout North America and Europe

Abstract: The environmental distribution of Dehalococcoides group organisms and their association with chloroethenecontaminated sites were examined. Samples from 24 chloroethene-dechlorinating sites scattered throughout North America and Europe were tested for the presence of members of the Dehalococcoides group by using a PCR assay developed to detect Dehalococcoides 16S rRNA gene (rDNA) sequences. Sequences identified by sequence analysis as sequences of members of the Dehalococcoides group were detected at 21 sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
315
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 404 publications
(330 citation statements)
references
References 39 publications
(47 reference statements)
10
315
1
4
Order By: Relevance
“…4b). These cultures showed complete dechlorination, thus confirming previous reports that bacteria of the Dehalococcoides group are the only known microorganism to completely dehalogenate PCE to ethene (Holliger et al 1999;Löffler et al 2000;Maymó-Gatell et al 2001;Hendrickson et al 2002;Smidt and de Vos 2004;Schmidt et al 2006). During 28 weeks and anaerobic transformation of approximately 60 mg/L PCE, the Dehalococcoides spp.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…4b). These cultures showed complete dechlorination, thus confirming previous reports that bacteria of the Dehalococcoides group are the only known microorganism to completely dehalogenate PCE to ethene (Holliger et al 1999;Löffler et al 2000;Maymó-Gatell et al 2001;Hendrickson et al 2002;Smidt and de Vos 2004;Schmidt et al 2006). During 28 weeks and anaerobic transformation of approximately 60 mg/L PCE, the Dehalococcoides spp.…”
Section: Discussionsupporting
confidence: 87%
“…It has been shown recently that in the field, often several dechlorinating bacteria are present simultaneously (Rouzeau-Szynalski et al 2011). In the environment, the reductively dechlorinating bacteria have been detected in different compartments, mainly in contaminated soil (Löffler et al 2000;Hendrickson et al 2002) and polluted groundwater (Schmidt et al 2006;Schmidt and Tiehm 2008;Vancheeswaran et al 1999). For river sediments, their occurrence in the Dutch part of the Rhine River (Holliger et al 1993), the Red Cedar, Père Marquette (Löffler et al 2000), Tahquamenon and Pine Rivers in the USA, and the Perfume River in Vietnam (Griffin et al 2004) was reported.…”
Section: Introductionmentioning
confidence: 99%
“…All DNA samples were PCR-amplifiable as positive results were obtained by PCR with these primers. The Dehalococcoides specific primers Fp DGC 774 and Rp DHC 1212 were used to substantiate anaerobic VC dechlorination (Hendrickson et al, 2002). The same PCR conditions as in the original works were used (Hendrickson et al, 2002;Coleman and Spain, 2003a).…”
Section: Molecular Biology Methodsmentioning
confidence: 99%
“…The Dehalococcoides specific primers Fp DGC 774 and Rp DHC 1212 were used to substantiate anaerobic VC dechlorination (Hendrickson et al, 2002). The same PCR conditions as in the original works were used (Hendrickson et al, 2002;Coleman and Spain, 2003a). The DNA samples were also subjected to PCR with specific primers for the EaCoMT gene (CoM-F1L and CoM-R2E) which codes for the enzyme epoxyalkane:coenzyme M transferase that is involved in the aerobic degradation of VC and ethene (Coleman and Spain, 2003b;Danko et al, 2006).…”
Section: Molecular Biology Methodsmentioning
confidence: 99%
See 1 more Smart Citation